Define colony number of subterranean termites coptotermes gstroi (Isoptera: Rhinotermitidae) in selected infested structures - Abdul Hafiz Ab Majid,; Abu Hassan Ahmad, (Universiti Kebangsaan Malaysia, 2015)
Termites are one of the social insects living in large colonies that can cause economic loss. The objective of this study was to estimate foraging territory of infested subterranean termites on building structure. A mark-recapture study was conducted on eight Coptotermes gestroi colonies located at selected infested building structures in Penang, Malaysia. From the foraging study, the population of C. gestroi was estimated to be within the range of 106,592±6,968 to 4,185,000±2,127,328. Additionally, the foraging territory was from 13 to 300 m2 of the infested building structures. Meanwhile the maximum foraging distance was from 4 to 30 m of the infested structures. The results indicated that each of the building structures was infested by a single colony. This study also showed that the triple mark recapture technique used to estimate the population size of the termite colony was capable of providing rough estimates of foraging population of C. gestroi.